Effect of Gender Exploitation and Violence on Health Status of Women and Girls in Chitwan District - Parajuli, Govinda Prasad; Chapagain, Sarita (Saptagandaki Journal, 2018)
This study aimed to findout forms and causes of gender exploitation and violence as well as reveal the effect of gender exploitation and violence on the health status of women and girls. The researcher collected secondary data from District Police Office and Women Cell of the same office of Chitwan. Primary data was collected from purposive sampling method. The study reveals that majority of the victims of exploitation and violence suffers from grave physical health problem, psychological and mental health problem and reproductive health problems. Similarly, the study also reveals that the causes of gender exploitation and violence are economical, political, educational and social backwardness. From the research, it is concluded that women and girls are dominated due to lack of education, patriarchal society, polygamy society, sexual dissatisfaction and dowry. Moreover, women are discriminated from birth. This study also shows that literate women are equally victimized as well as the illiterate women and girls. The Sapta Gandaki Journal Vol. IX, 2018 Feb. Page: 26-33